A Bibliometric Review of Heritage Language Studies: in the Field of Language Education - Ramadhani, Rizki Putri; Pamungkas, Alim Harun; Aryawan, Fatah Nasikh (Global Action and Education for Society, 2025)
Transnational migration has led to the emergence of diaspora families across various countries, bringing with them their original cultural identities, including their native languages. Within these families, the language is maintained and transmitted to subsequent generations as a heritage language. This study aims to analyze the development of research on heritage language in the field of language education through a bibliometric approach. The main reason for this research is to understand trends, dominant topics, and the interconnectedness of themes in heritage language studies, as well as to map scientific contributions over the past three decades. The method used is bibliometric analysis utilizing data from Google Scholar accessed via the Publish or Perish (PoP) 8 software and visualized using VOSviewer 1.6.18. A total of 450 documents from 1991 to 2025 were collected and analyzed based on citations, keywords, and co-occurrence among themes. The results show a significant increase in the number of publications in recent years, peaking in 2018. The keyword ‘learner’ emerged as a dominant node in the co-occurrence network, with strong links to concepts such as heritage language student, language ideology, and language maintenance. Additionally, a close relationship was found between the themes of heritage language education and heritage language policy, indicating a significant conceptual connection between language policy within families and the effectiveness of heritage language education. This study affirms the importance of a multidisciplinary approach in understanding and supporting the sustainability of heritage languages in multilingual societies.